Sistem Forecasting Keuangan Inventaris Sarana dan Prasarana dengan Metode Naive Approach pada Universitas CIC - Wibawa, Sakti; Sokibi, Petrus (Teknik Informatika Universitas Pamulang, 2020)
University Catur Insan Cendekia (UCIC) is a university located at Kesambi street number 202 Cirebon city. As one of the new universities in Cirebon city of course, would need inventory records of facilities and infrastructure that’s what at the university. Additionally, records spending on facilities and infrastucture costs is important. To optimize that cost recording requires a system. To Improve management facilities and infrastructure requires data related to facilities conditions and infrastructure. Naïve’s own method was the result of his prediction of the previous year’s real data as a benchmark for forecasting the following year. The process of this method is to collect the data of the cost of facilities and infrastructure spending first, after which the system will predict the cost of facilities and infrastructure using the formula N= t-1, in addition to this web based research using the framework codeigniter. The forecast method conducted in the study using the naïve approach method, which is more effective than the moving average method. Naïve’s method was used to predict the cost data of facilities and infrastructure available at UCIC. The study also had the naïve approach prediction reached the following year’s prediction.